Perbandingan efektifitas bahan bleaching karbamid peroksida 5% dan 10% terhadap perubahan kecerahan warna pada tumpatan resin komposit nanohybrid - Mangatas Halomoan Parluhutan Hutagalung; Tia Safitri; Susiani Tarigan (Prima Journal of Oral and Dental Sciences, 2019)
Composite resin is one of the restorative material that often used in dentistry that can obtain material fillings color matches the color of natural teeth. Composite resin has easy to absorb liquid which can caused discoloration in composite resin. Carbamide peroxide can be selected in home bleaching procedure to resolve ekstrinsic discoloration that goes on the surface of the composite resin. The study was aimed to see the comparison of the effectiveness carbamide peroxide 5% and 10% to the changes of nanohybrid composite resin brightness. This study were used an experimental design the pretest-posttest group design with total sample in this study was 30 of nanohybrid composite resin disk with 5mm diameter and 2mm thickness with 10 disk in each group. Group 1 as control group stored in artificial salivary solution, group 2 was applied with 5% of carbamide peroxide and group 3 was applied with 10% of carbamide peroxide,each samples applied for 8 hours and then stored in artificial salivary solution for 16 hours until 21 days and measured using chromameter on day 14 and day 21. The result of this research using Independent T-test and shows a significant difference before and after treatment with carbamide peoxide 5% and 10% with average result before treatment with 5% carbamide peroxide was 64.07±1,353 and after treatment is 69,34±0,869 and for the traetment with 10% carbamide peroxide before treatment was 63,84±0,701 and after treatment is 73,09±1,340. Higher concentration of carbamide peroxide can increase better brightness of the composite resin.